(untitled) (LEARNing Landscapes, 2022)
Poetic Inquiry invites people to return to the thousand-yearlong scholarly activity, namely writing original poetry. It encourages multiple possibilities of combining lexical thinking, poetry composition, and translation. In an attempt to revive the glory of writing, Poetic Inquiry appeals to a broader readership of scholarly works. This article explores my scholarly and daily life and seeks to learn by writing original poems. It also analyzes how I translate my Chinese poetry into English. With poetic works, I travel across languages, time, and space toward a better understanding of myself and the world.